Barriers and facilitators to opportunistic chronic kidney disease screening by general practice nurses. Issue 10 (October 2017) - Sinclair, Peter M; Day, Jenny; Levett‐Jones, Tracy; Kable, Ashley
Abstract: Aim: Opportunistic screening in general practice (GP) is a cost‐effective and viable approach to the early identification of chronic kidney disease (CKD). This study sought to identify the barriers and facilitators to CKD screening practices of GP nurses working in a regional area of New South Wales, Australia. Methods: An eight‐item elicitation questionnaire informed by the Theory of Planned Behaviour was administered to a convenience sample of 26 GP nurses. Results: Participants identified that the advantages of CKD screening were its early detection and treatment, the reduction of disease burden, and the opportunity to increase awareness and provide disease prevention education. These positive attitudinal beliefs were offset by negative beliefs about the impost of opportunistic screening on nursing time, particularly when there were other competing clinical priorities. Participants reported that practice doctors were wary of the financial costs associated with additional non‐claimable services and believed that unfunded services, regardless of patient benefit, were difficult to justify in a private business environment. Screening was enabled in GP settings with existing screening protocols or initiatives, and when patients presented with known risk factors. Barriers to screening were more frequently described and illustrated a strong focus on financial aspects of GP. Without reimbursement through the Medicare Benefits Scheme, screening was not considered an economical use of nursing time. Other competing and billable clinical services took precedence. Conclusion: The findings of this study can be used to inform the development and evaluation of interventions that target opportunistic CKD screening in the GP setting. Summary at a Glance: Sinclair et al identified barriers and facilitators to opportunistic CKD screening by general practice nurses from both small and large General Practice settings in regional New South Wales, Australia. The Theory of Planned Behaviour (TPB) provided the theoretical framework for the generation of data for this study.